Evaluation of Different Automation Methods Applied to BIM Based on Design Science - Gonçalves dos Santos, Victor (2023)
The BIM process was created in order to keep up with the growing demand for more technological and more complex projects in civil construction. In conjunction with this process, software such as Revit® was created, which features various tools and the possibility of adding new functions, using open source programming. This article aims to assist in choosing a tool for automation applied to Revit® software, using Design Science as a methodology. A four-step process is proposed for the development and evaluation of a BIM artifact. In the proposal idealization stage, the artifact was applied, using parameters such as the level of programming knowledge and the project needs to identify the best approach to creating an automation routine. The descriptive method of evaluating the artifact was used, where three scenarios were presented, based on real situations monitored in a company in the field of 3D modeling and project coordination. Finally, it was concluded that the proposal presented is valid in the creation of automation routines, as long as there is repetition in the activity to be automated.